Gender equality and religion: a multi-faith exploration of young adults’ narratives - Page, Sarah-Jane; Yip, Andrew Kam-Tuck (Sage, 2017)
This paper presents findings from research on young adults in the UK from diverse religious backgrounds. Utilizing questionnaires, interviews, and video diaries it assesses how religious young adults understood and managed the tensions in popular discourse between gender equality as an enshrined value and aspirational narrative, and religion as purportedly instituting gender inequality. We show that, despite varied understandings, and the ambivalence and tension in managing ideal and practice, participants of different religious traditions and genders were committed to gender equality. Thus, they viewed gender-unequal practices within their religious cultures as an aberration from the essence of religion. In this way, they firmly rejected the dominant discourse that religion is inherently antithetical to gender equality.